AN ANALYSIS OF THE TRANSLATION TECHNIQUE USED BY STUDENT IN TRANSLATING POETRY TEXT ENTITLED “EQUIPMENT’ BY EDGAR ALBERT GUEST - Virga Putra Darma; Salsabila Nuravianti (Tomorrow's Education Journal, 2023)
This is a qualitative research with discourse analysis methodes as a research design. The data that is used in qualitative research come from a range of collection methods. The reason for using a qualitative method is because qualitative research is more all encompassing since it includes information from numerous sources to pick up a more profound understanding from a person counting viewpoints and states of mind (Nassaji, 2015). This study aims to analyze translation technique used by students in poetry text Entitled “Equipment” by Edgar Albert Guest. In accordance with the research title related to translation techniques, the researcher will analyze the translation technique in the text of the poetry by Edgar Albert guest with the title "Equipment" which was translated by a student, in this section the researcher analyzes what translation techniques are used by participants from English to Indonesian with different translation techniques for each lyric in the text of the poetry. Based on the data that has been analyzed, there is a conclusion that there are six types of translation techniques used by participants including namely Amplification, compensation, linguistics compression, particularization, established Equivalent, modulation. Each of these six translation techniques has different accumulations, based on the diagram amplification occupies the highest position with a total score of 80, Linguistics compression is in second place with a total score of 70, Compensation and particularization are in third position with a total score which is equal to 60, modulation is in fourth position with a total score of 50, and established equivalent is in last position with a total score of 10. The conclusion is that amplification gets the highest position and established equivalent is in the lowest position.